Evaluasi Program Bantuan Langsung Tunai (BLT) dalam Membantu Perekonomian Masyarakat di Desa Sena Kecamatan Batang Kuis Kabupaten Deli Serdang - Batubara, Muhammad Anggara; Wulandari, Novita; Situmorang, Mulkan Andika (Mahesa Research Center, 2025)
The Village Fund Direct Cash Assistance (BLT) is a social protection program that aims to help the poor meet basic needs and reduce economic impacts, especially after the pandemic. However, the implementation of the Village Fund BLT in Sena Village, Batang Kuis District, Deli Serdang Regency, still faces various challenges, such as the validity of recipient data, transparency of distribution, and the effectiveness of assistance in improving community welfare. This study uses the CIPP (Context, Input, Process, Product) evaluation model to evaluate the extent to which the Village Fund BLT has achieved its goals. The research method used is qualitative descriptive, with data collection techniques through interviews, observations, and documentation. The results of the study show that BLT Village Funds are useful in the short term, but have not been able to improve community welfare sustainably. There are still obstacles in collecting recipient data, delays in disbursement, and a lack of assistance in the use of the assistance. Therefore, it is necessary to integrate BLT with economic empowerment programs, such as skills training and access to business capital, so that this program is not only consumptive but also contributes to sustainable village economic development.